2010
DOI: 10.1002/ijc.25711
|View full text |Cite
|
Sign up to set email alerts
|

High susceptibility to azoxymethane‐induced colorectal carcinogenesis in obese KK‐Ay mice

Abstract: Obesity is associated with colon carcinogenesis. However, not much information is available regarding the mechanisms of obesity-associated colorectal cancer, and there are only few useful animal models for investigating the underlying mechanism between obesity and colorectal cancer. KK-A y mice exhibit severe obesity. Amount of visceral fat assessed by micro-computed tomography was almost 15 times higher than that of same aged C57BL/6J mice. Treatment with azoxymethane (AOM; 200 lg/mouse injected once a week f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 34 publications
0
24
1
1
Order By: Relevance
“…Teraoka et al (48) also demonstrated that an obese mouse model KK-A(y) that does have an intact leptin and leptin receptor has higher sensitivity to azoxymethane. However, caution must be applied in interpreting sensitivity to azoxymethane, as mouse strains do differ in sensitivity to this chemical dependent on liver metabolism and DNA repair mechanisms (49,50) .…”
Section: Adipokine Regulation Of Colon Tissuementioning
confidence: 98%
“…Teraoka et al (48) also demonstrated that an obese mouse model KK-A(y) that does have an intact leptin and leptin receptor has higher sensitivity to azoxymethane. However, caution must be applied in interpreting sensitivity to azoxymethane, as mouse strains do differ in sensitivity to this chemical dependent on liver metabolism and DNA repair mechanisms (49,50) .…”
Section: Adipokine Regulation Of Colon Tissuementioning
confidence: 98%
“…Specifically, Zucker obese rats, KK-Ay mice and HFD-fed mice all show an increased incidence of colon cancer following treatment with azoxymethane as compared to controls. 55,56 …”
Section: Obesity-related Inflammationmentioning
confidence: 99%
“…Moreover, there were no significant differences in mRNA levels of p27 and p53 between the middle and distal parts (data not shown). Comparing the numbers of ACF in AOM-treated lean C57BL/6J mice with those of KK-A y mice, KK-A y mice increased the number of ACF in the proximal and middle colon (Teraoka et al, 2011). However, the effect of pioglitazone on different portions of the colon in obese mice could not be explained.…”
Section: Discussionmentioning
confidence: 72%
“…Real-time PCR was carried out using a DNA Engine OpticonTM 2 (MJ Japan Ltd., Tokyo, Japan) with SYBR Green Real-time PCR Master Mix (Toyobo Co., Osaka, Japan). Primers for mouse adiponectin (5'-AGGATGCTACTGTTGCAAGCTCTC, (Teraoka et al, 2011;Niho et al, 2005;Turmelle et al, 2006;Xiao et al, 2009). To assess the specificity of each primer set, amplicons generated from the PCR reaction were analyzed for melting curves.…”
Section: Real-time Polymerase Chain Reaction Analysismentioning
confidence: 99%
See 1 more Smart Citation